Pengaruh Pengaruh Penggunaan Multi Metode Berbantuan Media Ular Tangga Untuk Meningkatkan Hasil Belajar Siswa - Ayu K.N, Zahrotun Khamidah; Afifah, Nur Fathin; Mubarok, Muhammad Shulhuddin; Irmaningrum, Rizka Novi (Pendagogia: Jurnal Pendidikan Dasar, 2023)
The Effect of Using Multi-Method Assisted by Snakes and Ladders Media to Improve Student Learning Outcomes. This experimental research aims to determine the effect of using snakes and ladders media on student learning outcomes. The design used is a true experimental design with a posttest only control design. This research was conducted on students (class VI A) and (class VI B) at MI Muhammadiyah 1 Sukodadi for the 2022-2023 academic year which consists of 2 parallel classes. The research sample was taken from two classes randomly which were then placed as two sample groups, namely the experimental group (class VI A) and the control group (class VI B). The instrument has been tested beforehand and validated empirically. Data analysis using the ???? test. The results showed that there was a significant effect of the use of Multimethod assisted by snakes and ladders media to improve student learning outcomes, in class VI MI Muhammadiyah 1 Sukodadi.